cos A π = 2 1 2 + 2 + 3
Find the positive value of A satisfying the equation above.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
An easy to follow solution for once! Horray!
cos A π = 2 1 2 + 2 + 3 ⟹
4 c o s 2 ( A π ) = 2 + 2 + 3 ⟹
4 c o s 2 ( A π ) − 2 = 2 + 3 ⟹
2 ( 2 c o s 2 ( A π ) − 1 ) = 2 + 3 ⟹
2 c o s ( A 2 π ) = 2 + 3 ⟹
4 c o s 2 ( A 2 π ) = 2 + 3 ⟹
4 c o s 2 ( A 2 π ) − 2 = 3 ⟹
2 ( 2 c o s 2 ( A 2 π ) − 1 ) = 3 ⟹
2 c o s ( A 4 π ) = 3 ⟹
c o s ( A 4 π ) = 2 3 ⟹
A 4 π = 6 p i ⟹
A = 2 4
Finding x , the straight way, would be a long journey finding inverse cos (arccos). Let's find the value of x , through inverse cos formula first.
cos ( x ) = 2 1 2 + 2 + 3 x = cos − 1 { 2 1 2 + 2 + 3 } Let 2 1 2 + 2 + 3 = y x = cos − 1 ( y ) Using inverse cos formula cos − 1 ( A ) = tan − 1 [ A 1 − A 2 ] ⟹ x = cos − 1 ( y ) = tan − 1 [ y 1 − y 2 ] Then we find value of arctan using Taylor series y = 2 1 2 + 2 + 3 ≈ 0 . 9 9 1 4 Now let’s attempt to find value of cos − 1 ( y ) tan − 1 [ y 1 − y 2 ] = tan − 1 [ 0 . 9 9 1 4 1 − ( 0 . 9 9 1 4 ) 2 ] = tan − 1 [ 0 . 9 9 1 4 0 . 0 1 7 1 2 6 0 4 ] = tan − 1 [ 0 . 9 9 1 4 0 . 1 3 0 9 ] = tan − 1 ( 0 . 1 3 2 ) Therefore, tan − 1 ( 0 . 1 3 2 ) = 0 . 1 3 2 − 3 ( 0 . 1 3 2 ) 3 + 5 ( 0 . 1 3 2 ) 5 − 7 ( 0 . 1 3 2 ) 7 + 9 ( 0 . 1 3 2 ) 9 ⟹ tan − 1 ( 0 . 1 3 2 ) ≈ 0 . 1 3 1 2 rad ∴ x = cos − 1 ( y ) = 0 . 1 3 1 2 rad ⟹ x ≈ 7 . 5 ∘ ∴ x = 2 4 π ⟹ A = 2 4
You can also do this the other way, coming in reverse starting with cos ( 2 1 5 ) or cos ( 2 4 π )
Problem Loading...
Note Loading...
Set Loading...
cos x cos 2 x 4 cos 2 x 4 cos 2 x − 2 2 ( 2 cos 2 x − 1 ) 2 cos 2 x 4 cos 2 2 x 4 cos 2 2 x − 2 2 cos 4 x cos 4 x ⟹ 4 x x = 2 1 2 + 2 + 3 = 4 2 + 2 + 3 = 2 + 2 + 3 = 2 + 3 = 2 + 3 = 2 + 3 = 2 + 3 = 3 = 3 = 2 3 = 6 π = 2 4 π
⟹ A = 2 4